The Greek Debt Restructuring: An Autopsy - Jeromin Zettelmeyer; Christoph Trebesch; Mitu Gulati (Center for Economic Studies and ifo Institute (CESifo), 2013)
The Greek debt restructuring of 2012 stands out in the history of sovereign defaults. It achieved very large debt relief - over 50 per cent of 2012 GDP - with minimal financial disruption, using a combination of new legal techniques, exceptionally large cash incentives, and official sector pressure on key creditors. But it did so at a cost. The timing and design of the restructuring left money on the table from the perspective of Greece, created a large risk for European taxpayers, and set precedents - particularly in its very generous treatment of holdout creditors - that are likely to make future debt restructurings in Europe more difficult.
Keywords: F34; 330; sovereign debt; sovereign default; crisis resolution; Greece